Investor Preference and Promoter's Ownership Pattern in Graded IPOs of India - Mittal, Sanjiv; Gupta, Naresh K.; Sharma, Sudesh Kumar (Indian Journal of Finance, 2012)
SEBI, the Indian securities market regulator, has set a unique example for the entire world by introducing IPO grading in India in 2006 on an optional basis, and further mandating it from May 2007. The purpose of this grading was to provide retail investors with a ready-made assessment of the fundamental quality of the issuer of an IPO, so that they could make a better and informed investment decision in an era of information overload. Grading of IPOs is subject to severe criticism. Critics question efficacy and effectiveness of this process. However, the findings of this paper suggest that IPO grading does influence investor preference and demand. Further, strong negative effect on post-issue promoter's ownership holding is noted. The paper infers that all investor classes, including retail investors, benefit from IPO grading.